Implementasi Kurikulum Al-Qur’an di TK Al-Ikhwan Kualuh Hilir dalam Membangun Karakter Islam Anak Usia Dini - Aziz, Mursal; Napitupulu, Dedi Sahputra; Khairani, Zamzam (Pendidikan Guru PAUD Universitas Persatuan Guru Republik Indonesia Semarang, 2025)
The Al-Qur'an curriculum implemented in early childhood education institutions can play a role in shaping Islamic character in children. This study aims to explore the implementation of the Al-Qur'an curriculum in Al-Ikwan Kindergarten Kualuh Hilir, North Labuhanbatu, in shaping Islamic character in early childhood. The curriculum is designed by integrating educational values that emphasize moral training, discipline, and basic understanding of Islamic teachings from an early age. This study uses a descriptive qualitative approach, with data collection techniques in the form of interviews with the principal, teachers and parents of students, observations conducted during the learning process and document reviews in the form of learning tools and curriculum. The research findings indicate that the implementation of the Al-Qur'an policy has a positive contribution to the development of Islamic character in children, which is reflected in their increased understanding of moral and religious values, as well as behavior that is in line with Islamic principles. The results of this study are expected to be a reference in the development of Islamic education curriculum in early childhood education to shape superior character based on Islamic teachings.